Effects of different types of warm-ups on performance by young volleyball players - Popelka, J.; Bujdos, G.; Pivovarnicek, P. (Journal of Human Sport & Exercise, 2024)
The study aimed to compare the impact of warm-up with dynamic stretching (DS), warm-up with foam roller (FR), and warm-up with a combination of FR and DS (CO) on the performance of movement indicators in tests conducted on young volleyball players (n = 8, age = 15.4 ± 0.5 years, height = 176.3 ± 8.6 cm, weight = 64.5 ± 10.9 kg) during the competition year 2021/2022. To assess the effects of warm-up methods (DS, FR, CO), performance in various movement tests was compared. The tests included the sit and reach test (SR), a 1 kg ball throw in a kneeling position (H1), squat jump (SJ), countermovement jump (CMJ), sit-up test (SU), E-Test (ET), and run to cones (RC). The One-way ANOVA analysis did not reveal significant differences in the effects of DS, FR, and CO warm-ups (p > .05) across all investigated indicators. The effect size coefficient (n2) indicated negligible differences (n2 < 0.01), except for the ET indicator, where a small effect size (n2 = 0.028, 95%CI: 0.04-0.31) favoured DS. These findings carry social importance as they contribute to enhancing the efficacy of warm-up routines, both in sports performance and health considerations.